2013
DOI: 10.2147/copd.s44022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a network system for providing proper inhalation technique by community pharmacists on clinical outcomes in COPD patients

Abstract: IntroductionNonadherence to inhalation therapy is very common in patients with chronic obstructive pulmonary disease (COPD). Few data are available to support the role of community pharmacists in optimizing inhalation therapy in COPD patients. Since 2007, the Kitano Hospital and the Kita-ku Pharmaceutical Association have provided a network system for delivering correct inhalation techniques through certified community pharmacists. The effects of this network system on clinical outcomes in COPD patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 27 publications
4
66
0
2
Order By: Relevance
“…With respect to IT, the offered interventions were found to significantly reduce IT errors or even improve the choice of the inhaler [5, 23-25, 28, 29]. For MA, the review showed that CPs interventions resulted in improving adherence to inhaled medications which was statistically significant in the addressed studies [8,23,25]. This is consistent with other studies which show that pharmacist-delivered interventions can lead to significant improvement in medications adherence in other diseases [30,31].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…With respect to IT, the offered interventions were found to significantly reduce IT errors or even improve the choice of the inhaler [5, 23-25, 28, 29]. For MA, the review showed that CPs interventions resulted in improving adherence to inhaled medications which was statistically significant in the addressed studies [8,23,25]. This is consistent with other studies which show that pharmacist-delivered interventions can lead to significant improvement in medications adherence in other diseases [30,31].…”
Section: Discussionsupporting
confidence: 60%
“…There was a clear emphasis from the reviewed studies on the need to provide patients with repeated instructions on correct IT by CPs and not to consider it as a one-time service in order to ensure sustainability [5,8,29]. The German study [5] in this review highlighted that patients benefited from IT education intervention irrespective of their previous education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhering to inhaled medications is one of the most important factors for managing COPD in both clinical and ambulatory settings. In a recent study, it was shown that there was a significant decrease in the frequency of dyspnea, cough, sputum purulence or wheeze [18].…”
Section: Introductionmentioning
confidence: 97%
“…This may lead to decrease disease control, increase the absenteeism from work or school, unnecessary increase in medication dosage, increase risk of side effects, non adherence to inhaled medication and exacerbations manifestations especially deterioration of dyspnea that requires oral corticosteroid treatment [17]. Many COPD patients are non adherent to the inhaled drugs so mortality rate is susceptible to increase more than twice among those patients compared to patients who adhere to the inhaled medications [18,19].…”
Section: Introductionmentioning
confidence: 99%